Micro-Politcal Acts in the Psychosocial Approach in El Progreso de Puntarenas - Alpízar Guerrero, Mariana (2018)
This writing arises from an effort made by various people and groups during the year 2017, from the execution of the LGBT-and-the-Port Student Initiative, held in the El Progreso area of Puntarenas in 2017, with an organization of civil society made up of LGBT people, cisgender women, sex workers and people with HIV- Positive, among other populations. The objective of this article is not only to present the results of this process, but also to propose the category of approach called micropolitical acts, in which methodologies are used as Participative Action Research, Critical Pedagogies, Post-structuralist Feminisms, among other theoretical-practical approaches. Concrete examples are used for the explanation of this proposal from a located place.